2015
DOI: 10.1002/ajh.24000
|View full text |Cite
|
Sign up to set email alerts
|

Complex karyotype, older age, and reduced first‐line dose intensity determine poor survival in core binding factor acute myeloid leukemia patients with long‐term follow‐up

Abstract: Approximately 40% of patients affected by core binding factor (CBF) acute myeloid leukemia (AML) ultimately die from the disease. Few prognostic markers have been identified. We reviewed 192 patients with CBF AML, treated with curative intent (age, 15-79 years) in 11 Italian institutions. Overall, 10-year overall survival (OS), disease-free survival (DFS), and event-free survival were 63.9%, 54.8%, and 49.9%, respectively; patients with the t(8;21) and inv(16) chromosomal rearrangements exhibited significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 47 publications
6
46
0
1
Order By: Relevance
“…There is evidence indicating that auto-HSCT is able to significantly reduce relapse risk in AML with favorable cytogenetics, which still carry disease recurrence rates up to 35–40 % following conventional chemotherapy, with a particular risk for core-binding factor (CBF) AML with adverse prognostic features [39] or positive MRD after consolidation chemotherapy [40]. Further, there is data suggesting that in NPM1-mutated and CEBPA double-mutated (CEBPAdm) AML, the high chemosensitivity of the disease might be exploited with auto-HSCT intensification [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence indicating that auto-HSCT is able to significantly reduce relapse risk in AML with favorable cytogenetics, which still carry disease recurrence rates up to 35–40 % following conventional chemotherapy, with a particular risk for core-binding factor (CBF) AML with adverse prognostic features [39] or positive MRD after consolidation chemotherapy [40]. Further, there is data suggesting that in NPM1-mutated and CEBPA double-mutated (CEBPAdm) AML, the high chemosensitivity of the disease might be exploited with auto-HSCT intensification [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…К настоящему времени к прогностически неблагоприятным факторам относятся наличие дополнительных хромосомных нарушений, прежде всего делеции del(9)(q22), трисомии некоторых хромосом, а также сложные нарушения кариотипа [2,3,[10][11][12][13][14]. Что же касается молекулярных маркеров, то про-гностически неблагоприятными являются мутации генов ASXL, BAALC, c-KIT, FLT3 [3,13].…”
Section: Introductionunclassified
“…Complex cytogenetic abnormalities are also found in CBF-AML and have been shown to adversely affect long-term survival in some studies. 33,34 Interestingly, we observed that among our CBF-AML patients (n=27), lower HLTF expressors also had more secondary chromosome abnormalities (1.46 vs. 0.5) and higher chances of carrying a complex karyotype (23% vs. 0%) involving three or more additional aberrations than higher HLTF expressors. These observations suggest broad impacts of HLTF reduction on chromosomal instability across AML subtypes.…”
Section: Discussionmentioning
confidence: 71%